THE EVOLUTION OF AVIANCA AIRLINES IN TERMS OF THE EVOLUTION OF ITS CONTEXT - Ospina Holguín, Javier Humberto (2015)
The purpose of this article is to present the evolution of the Colombian airline Avianca as a function of the evolution of its context. Based on a selected bibliography and press excerpts, an analysis of the trajectory of the company expressed in terms of the dynamics of its historic setting is done, an analysis inspired by constructivist and sciences of complexity considerations. Aspects such as the First and Second World Wars, technological developments, US imperialism and the political and national economy fundamentally forge the trajectory of the company between 1919 and 1940; while technological developments, the monopolistic nature of the sector and the struggles between the major national business groups, the adoption of economic openness, labor relations and laws, drug trafficking and international terrorism and the oil crisis do so in the period 1940-2014. It is concluded that Avianca is a “pro-cyclical” company especially marked by the evolution of the socio-economic factor of its environment, but other factors significantly influence its evolution.